Urban Policy and Mobility Justice for People Experiencing Homelessness in Accessing Essential Services: A Systematic Review and Bibliometric Analysis - Indah Ashlachal Ummah; Harsuko Riniwati; Agung Murti Nugroho; Andik Isdianto (JAMBURA GEO EDUCATION JOURNAL, 2026)
This study aims to analyze research trends and formulate policy strategies for homeless mobility in accessing basic services sustainably in public spaces. Existing systematic reviews are generally partial, focusing only on clinical health aspects or housing availability issues. However, there are very few comprehensive studies examining the mobility of the homeless in accessing basic services in public spaces. This study used a Systematic Literature Review (SLR) method with data from Scopus filtered through the PRISMA protocol, resulting in 25 relevant articles being selected. Bibliometric analysis was conducted using VOSviewer and RStudio (Bibliometrix), followed by thematic analysis for policy synthesis. The results indicate a steady annual growth rate of 8.01% from 2016 to 2025, in international collaboration remains low (8%), reflecting a localized research focus. The results show fluctuations in scientific production with a significant peak in 2022, but reveal a knowledge gap (research gap) where the integration of public space and mobility remains a minor (niche) theme compared to health issues. The policy strategies are divided thematically into social, environmental, educational, and economic aspects. This study recommends more concrete practical implications, including the provision of inclusive public transportation, elimination of exclusionary architecture, and simplification of bureaucracy for accessing basic services. In conclusion, city policy must shift from mere order-based management to fulfilling the right to the city through cross-sector collaboration that ensures the welfare of vulnerable groups in the city